2010
DOI: 10.1104/pp.110.160663
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Arabidopsis RACK1 in Protein Translation and Its Regulation by Abscisic Acid      

Abstract: Earlier studies have shown that RACK1 functions as a negative regulator of abscisic acid (ABA) responses in Arabidopsis (Arabidopsis thaliana), but the molecular mechanism of the action of RACK1 in these processes remains elusive. Global gene expression profiling revealed that approximately 40% of the genes affected by ABA treatment were affected in a similar manner by the rack1 mutation, supporting the view that RACK1 is an important regulator of ABA responses. On the other hand, coexpression analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
133
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 63 publications
3
133
0
3
Order By: Relevance
“…Thus, Arabidopsis RPL10 proteins are functionally equivalent to the RPL10 from S. cerevisiae and, therefore, these proteins are interchangeable. Similarly, the three Arabidopsis RACK1 proteins, which are components of the 40S ribosome subunit, complement S. cerevisiae cross pathway control2/rack1 mutants, as was shown previously for the mammalian RACK1 protein (Gerbasi et al, 2004;Guo et al, 2011). However, although all three Arabidopsis genes are functional in rescuing yeast lethality, slower growth rates were observed when compared with that obtained using the endogenous yeast protein, indicating differences in the complementation efficiency.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, Arabidopsis RPL10 proteins are functionally equivalent to the RPL10 from S. cerevisiae and, therefore, these proteins are interchangeable. Similarly, the three Arabidopsis RACK1 proteins, which are components of the 40S ribosome subunit, complement S. cerevisiae cross pathway control2/rack1 mutants, as was shown previously for the mammalian RACK1 protein (Gerbasi et al, 2004;Guo et al, 2011). However, although all three Arabidopsis genes are functional in rescuing yeast lethality, slower growth rates were observed when compared with that obtained using the endogenous yeast protein, indicating differences in the complementation efficiency.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, it has been recently demonstrated that ribosomal proteins control auxinmediated developmental programs by translational regulation of auxin response factors (Rosado et al, 2012). In addition, the characterization of single, double, and, in certain cases, triple mutants as well as complementation by paralog genes have demonstrated full, partial, and no redundancy between members of ribosomal protein families (Briggs et al, 2006;Guo and Chen, 2008;Guo et al, 2011;Horiguchi et al, 2011;Stirnberg et al, 2012).…”
mentioning
confidence: 99%
“…The genes within the two subnetworks were highly connected to each other and to a limited set of other genes. For subnetwork 1, one of these other genes, GRMZM2G038032, shows homology to Arabidopsis RECEPTOR FOR ACTIVATED C PROTEIN KINASE1 (RACK1) genes involved in ribosome biogenesis (Guo et al, 2011); it was shown that lossof-function mutations in RACK1 genes in Arabidopsis severely affect rosette leaf production and root growth (Guo and Chen, 2008). The ribosomal genes in this first subnetwork were also highly connected to GRMZM2G067877, a homolog of an Arabidopsis mitochondrial adenine nucleotide transporter (ADNT1) that plays a role in energy supply in heterotrophic tissues.…”
Section: Toward a Robust Growth Regulatory Networkmentioning
confidence: 99%
“…5 eIF6 binds RACK1 5,23 that resides on 48S subunits. 24 This model places eIF6 activity downstream of the growth factor/PKC signaling cascade and explains observations indicating that eIF6 can repress translation in vitro but not in vivo when ras/PKC stimulation is performed (see below).…”
Section: S Formation and Diseasementioning
confidence: 99%